Industrial Policy Options for Developing Countries: The Case of the Automotive Sector in Thailand & Malaysia - Fuangkajonsak, Wanrawee (Tufts Archival Research Center, 2007)
Submitted in partial fulfillment of the degree Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: Industrial policies are formulated in order to guide the course of economic development. In a country whose government has industrial policies, the market force is more or less distorted due to government intervention. It can also be the case that the government uses industrial policy to correct market distortion resulted from domestic monopoly. However, there is no uniformity in the essence or the extent of industrial policies. Different paths chosen by the governments lead to different patterns of industrial development. Even similar strategies could bring about different results when implemented under different environments. This thesis focuses on the policy options for developing countries in particular. The options studied here are the extent of the government's involvement in industrial development. The case study of the automotive sector in Thailand and Malaysia reveals that Malaysian state entrepreneurship, through the national car projects, hinders the development of the industry competitiveness. When the government gets involved in production, domestic competition is limited in order to protect its interests. Thus, the protected producers are not under pressure to upgrade their production capabilities. Further, it incurs greater burden on domestic consumers by raising domestic vehicle prices, yet creates less jobs than the Thai policy does. On the contrary, by staying out of production activities, the Thai state is able to draw the line between public and private interests. It encourages competition in the domestic market and was able to introduce liberalization to the industry earlier than the Malaysian state. The local producers, hence, are forced to improve their products in order to survive and the industry thereby experiences rapid expansion, contributing greatly to employment in the country.